ENGARUH KETINGGIAN TEMPAT DAN SISTEM PEMELIHARAAN TERHADAP KORELASI GENETIK BOBOT LAHIR DENGAN BOBOT DEWASA SAPI BALI THE EFFECT OF ALTITUDES AND CARE SYSTEM ON THE GENETIC CORRELATION BETWEEN BIRTH WEIGHT AND PARENTAL BODY WEIGHT OF BALI CATTLE - Franky M.S. Telupere (Universitas Nusa Cendana, 2014)
A research has been done to estimate the genetic correlation between birth weight and parental bodyweight of bali cattle with survey method by procedures observation, measurements, and interviews inhighland (Kabupaten Timor Tengah Selatan) and lowland (Kabupaten Kupang) at difference care system(semi intensive and extensive). Four hundred eighty bali cattle were use in this research. The results showedthat no significance differences (P>0.05) on sire and dam body weight based on altitudes, care system, andinteraction between altitudes and care system. However, the birth weight had significant differences(P<0.05) whereas in highland at semi intensive care system the value was better than extensive system.Estimation of the phenotype correlation between birth weight and parental body weight at semi intensivecare system showed a high positive value whether in highland or in lowland for all estimation components.While for extensive care system, the estimation based on sire component produced a negative value. Thephenotype correlation values based on dam component was better than sire or sire-dam components. Thegenetik correlation values for semi intensive care system showed a positive value, on the other hand anegative value was found in extensive care system